2013
DOI: 10.3354/dao02557
|View full text |Cite
|
Sign up to set email alerts
|

Batrachochytrium dendrobatidis in amphibians of Cameroon, including first records for caecilians

Abstract: Amphibian chytrid fungus Batrachochytrium dendrobatidis (Bd) has been hypothesised to be an indigenous parasite of African amphibians. In Cameroon, however, previous surveys in one region (in the northwest) failed to detect this pathogen, despite the earliest African Bd having been recorded from a frog in eastern Cameroon, plus one recent record in the far southeast. To reconcile these contrasting results, we present survey data from 12 localities across 6 regions of Cameroon from anurans (n = 1052) and caecil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Many of the sampled genera have previously been shown to be infected with Bd in other African regions (e.g. : Amietophrynus (mean prevalence 21.05%; Bayesian credible interval 11.13–36.46%), Hyperolius (39.51%; 35.26–43.92), Leptopelis (28.57%; 22.03–36.18%), Petropedetes (11.11%; 15.17–65.11%), Phrynobatrachus (17.65%; 9.63–30.32%), Ptychadena (26.26%; 20.36–33.17%), Xenopus (3.35%; 2.35–4.77%) [calculated from 26], [27], [28], [29], [85], [86], [90], [91], [92]). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the sampled genera have previously been shown to be infected with Bd in other African regions (e.g. : Amietophrynus (mean prevalence 21.05%; Bayesian credible interval 11.13–36.46%), Hyperolius (39.51%; 35.26–43.92), Leptopelis (28.57%; 22.03–36.18%), Petropedetes (11.11%; 15.17–65.11%), Phrynobatrachus (17.65%; 9.63–30.32%), Ptychadena (26.26%; 20.36–33.17%), Xenopus (3.35%; 2.35–4.77%) [calculated from 26], [27], [28], [29], [85], [86], [90], [91], [92]). …”
Section: Resultsmentioning
confidence: 99%
“…These are complemented by very recent additions from Nigeria [24], [25], [26], Cameroon [27], [28] and Gabon [29] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Cameroon has one of the oldest records for this pathogen, recorded in a frog collected from eastern lowland Cameroon in 1933 (Soto-Azat et al 2010). A 2006 survey of amphibians on Mt Oku found no evidence for the presence of this pathogen (Doherty-Bone et al 2008) but subsequent sampling has found it to be present at a prevalence comparable to other regions of Africa (Doherty-Bone et al 2013a; Hirschfeld et al 2016). However, the role of Bd in amphibian population viability in Cameroon is still cryptic due to new findings that multiple strains of varying virulence occur within Africa (Farrer et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of strains of this fungus from localities in Cameroon is now a priority to understand if strains are from hyper-virulent or benign variety (one sample was said to be from the pan-global hypervirulent strain, but was not accompanied by peer-reviewed data in Hirschfeld et al 2016). Using archived museum specimens to determine the long-term history of this pathogen on Mt Oku will test the endemic versus novel pathogen hypothesis in Cameroon (Soto-Azat et al 2010; Doherty-Bone et al 2013a). Research on the susceptibility of Cameroonian amphibians to infection by Bd could also take place, particularly the presence of skin peptides and microbiota that provide resistance to this fungal pathogen (Harris et al 2006; Woodhams et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The role of this pathogen in the persistence of threatened amphibian populations in Cameroon and Africa in general remains uncertain (Doherty-Bone et al 2013), although the continued failure to detect Bd in X. longipes (n = 231 negative samples from 3 studies), despite sympatric infected anurans (including congener X. amieti, Table 3) suggests that this species is resistant to infection by this pathogen.…”
Section: Discussionmentioning
confidence: 99%